ESTIMACION DE LA PREVALENCIA DE ROTAVIRUS A EN POBLACIÓN INFANTIL DE FACATATIVA CUNDINAMARCA DE ENERO A DICIEMBRE DE 2002 - Chaparro, Amanda; Departamento de Microbiología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2004)
Due to the worldwide importance that Rotavirus A (RTVA) has acquired, as an infectious agent causing diarrhea on children under 5 years of age, in the present research, an epidemiologic follow up was done in order to know the prevalence of this virus in the town of Facatativa, Cundinamarca, between the months of January and December, 2002. Out of 212 samples analyzed, 40 positive samples were found, with a prevalence rate of 45.9 X 10.000 on children under 5 years of age. The urban zone had a higher number of cases by RTVA (28/148) than the rural zone (12/54). The highest number of  cases was presented between 13 and 24 months of age, with the same proportion for both boys and girls. The relation of the presence of RTVA with the variables: garbage disposal, excretes and water consumption, was not statistically relevant. The presence of RTVA in diarrhea did not have any relation with weather factors.